Petrology of the granitoid intrusions in the Shalair Valley area, northeastern Iraq - Abdulzahra, Imad Kadhim; Hadi , Ayten (Iraqi Journal of Science, 2022)
The granitoid bodies in the Shalair Valley are structurally located within so-called Iraqi Zagros Suture Zone, in the northeastern Iraq. One hundred and sixty-two representative samples were collected from five granitoid intrusive bodies in the valley: Aulan and Siristan in the northern part, Mishao and Laladar in the southern part and Demamna in the western part. Two major types of granitoids in the eastern and western part of the Shalair Valley area were indentified. The granitoids from the four locations in the eastern part, have similar mineral constitutes. These rocks are composed of plagioclase + quartz ± hornblende with two types of texture, equigranular texture represented by Aulan and Siristan in the northern part and porphyritic texture in the southern part represented by Mishao and Laladar. This reflects several stages of intrusive events, starting with stable fractional crystallization conditions represented by Aulan and Siristan granitic rocks with equigranular texture and a late stage of unstable crystallization conditions represented by Mishao and Laladar granitic rocks with porphyritic texture.Damamna granites in the western part have different mineral composition. They are composed of K-feldspar, quartz and small amount of plagioclase with graphic texture represented by the intergrowth between K-feldspar and quartz, which reflects simultaneous crystallization of K-feldspar and quartz from a silicate melt close to the eutectic point.